(untitled) (UNWE Yearbook, 2024)
The objective of this paper is to examine the impact of the Taxonomy (Regulation 2020/852) on business in the non-financial sector. It is a consecutive paper, written by the author on the topic of sustainability – the purpose of the company, the global value chains and the transition of the business model on the road to a climate neutral Europe. The regulators and the politicians see the Taxonomy mainly from the perspective of sustainable financing. Researchers and consultants analyze the new norms for sustainability as a driver for new financial products and an enabler for a better-functioning European Capital Market. The Taxonomy impacts the economic entities in the non-financial sector and shapes their priorities about sustainability. The implementation of the Taxonomy by the non-financial business is in the scope of the paper. Although the implementation period is short, it is important to examine how business reacts to the new norms of sustainability.